Situation-based Management in a Philosophical Framework A Critical Approach to Decision Making - Alberta Adinata; Uki Yonda Asepta; Agung Winarno (International Journal of Economics and Management Sciences, 2024)
Situation-based management is an approach that emphasizes the importance of context in managerial decision-making. In the philosophical view, this theory highlights that there is no one universal management method; instead, the effectiveness of managerial strategies depends largely on the specific conditions, values, and needs of the organization. By utilizing various philosophical perspectives, such as pragmatism, existentialism, and phenomenology, managers can be more adaptive in responding to environmental dynamics. This approach encourages managers to develop critical skills in situation analysis and ethical decision-making, in order to create added value for the organization and stakeholders. This research aims to explore how situation-based management can be integrated with philosophical principles in daily managerial practice.